Comparison of Intranasal and Intramuscular Immunization against Human Immunodeficiency Virus Type 1 with a DNA-Monophosphoryl Lipid A Adjuvant Vaccine - Sasaki, Shin (American Society for Microbiology, 1998)
We compared immune responses to intranasal and intramuscular DNA vaccinations against human immunodeficiency virus type 1 with monophosphoryl lipid A (MPL) used as an adjuvant. Both routes of vaccination resulted in similar levels of cell-mediated immunity, but the intestinal secretory immunoglobulin A response was higher following intranasal immunization than after intramuscular immunization. MPL demonstrated its adjuvanticity in vaccination by both routes.